Is 'Employment during Motherhood' a 'Value Changing Experience'? - Mireia Borrell-Porta; Valentina Contreras; Joan Costa-i-Font (Center for Economic Studies and ifo Institute (CESifo), 2021)
Does employment during motherhood change peoples preferences? We study whether the experience of employment during motherhood exerts an effect on attitudes towards gender norms, and more specifically, attitudes towards the impact of women's employment on children's wellbeing (which proxy traditional gender attitudes). Drawing on a large, representative and longitudinal data and an instrumental variable (IV) strategy that exploits a Bartik instrument for employment, we find that, that non-mothers who work and mothers who do not work are more likely to agree that pre-school children suffer if mothers work, which we proxy as having more traditional views. However, this is not the case when women experience both working and motherhood it does not significantly change women's attitudes. These results suggest that exogenous changes in employment during motherhood confirm individuals priors, and point towards the critical role of early life value formation. That is, employment during motherhood is not a "value changing experience" but rather a "value preserving experience". Hence, the so-called 'motherhood penalty' cannot be fully explained by a change in attitudes after employment during motherhood.
Keywords: Z10; J22; 330; attitude formation; value changing experiences; confirmation bias; women employment attitudes; women employment after maternity; later life attitudes; children